Identification of Mycobacterium Tuberculosis Complex Infection in Human By Indirect ELISA Using Low Molecular Weight Proteins from Culture Filtrate of Mtb Strain C - Mozhgan Khosrobeygi; Nader Mosavari; Mitra Salehi; Naheed Mojgani; Majid Akbari (Journal of Mazandaran University of Medical Sciences, 2022)
Background and purpose: Tuberculosis is one of the major global health problems with high mortality. Establishing a rapid and low-cost identification method is significant, especially in developing countries. In this study, we aimed to design an indirect ELISA system with low molecular weight antigens secreted by Mycobacterium tuberculosis strain C, for identification of Mycobacterium tuberculosis Complex infection in human. Materials and methods: The secretory proteins from culture filtrate of Mtb strain C extracted by Sephadex-G50 were used as target antigen in designing an indirect ELISA system. Then, human sera with tuberculin skin test, culture, acid-fast bacilli smear, and PCR test results were selected to detect human serum antibodies against these low molecular weight proteins. Results: During gel chromatography and SDS-PAGE (12.5%) analysis, the purified protein F2 fractions with approximately 0.7 mg/ml and molecular weights in the range of 14-40 kDa were used as the target antigen in designing the indirect ELISA system. The ELISA system designed by F2 showed 78% sensitivity and 92% specificity in identifying tuberculosis. Conclusion: The ELISA results based on low molecular weight proteins, with the sensitivity and specificity achieved in this study, might support the hypothesis that the Mtb culture filtrate antigens could be used as a rapid and sensitive assay in ELISA test for detection of pulmonary TB.